2005
DOI: 10.1162/1088198054084590
|View full text |Cite
|
Sign up to set email alerts
|

Indirect and Direct Energy Requirements of City Households in Sweden: Options for Reduction, Lessons from Modeling

Abstract: Summary The objective of this article is to explore the potential for lowering household energy use given existing local support systems, in this case in the Stockholm inner city with the aid of the Dutch energy analysis program (EAP) that was adapted to Swedish conditions and that portrays total energy use for 300 consumption categories. Previously such modeling for Sweden was carried out using only Dutch databases. Our case‐study area is well equipped with food stores, local markets, public transportation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…An overview of the current research provides strong evidence that shifting food consumption patterns toward a less meat-heavy diet can have potential positive effects on individual carbon balances and other environmental impacts such as land, water, fossil fuel and chemical input use (Goodland 1997;Dutilh & Kramer 2000;Tukker et al 2011;Carlsson-Kanyama 1998;Carlsson-Kanyama et al 2005). Studies have shown, for instance, that the livestock sector contributes as much as 18% of global anthropogenic greenhouse gas emissions (Steinfeld et al 2006), that animal-based ingredients have ten times higher energy requirements than plant-based ones (Dutilh & Kramer 2000), and that the difference between an affluent, meat-heavy diet and a vegetarian one ranges between a threefold and eightfold higher need for land (Gerbens-Leenes et al 2002).…”
Section: Sustainable Food Consumption -An Effective Policy Option?mentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the current research provides strong evidence that shifting food consumption patterns toward a less meat-heavy diet can have potential positive effects on individual carbon balances and other environmental impacts such as land, water, fossil fuel and chemical input use (Goodland 1997;Dutilh & Kramer 2000;Tukker et al 2011;Carlsson-Kanyama 1998;Carlsson-Kanyama et al 2005). Studies have shown, for instance, that the livestock sector contributes as much as 18% of global anthropogenic greenhouse gas emissions (Steinfeld et al 2006), that animal-based ingredients have ten times higher energy requirements than plant-based ones (Dutilh & Kramer 2000), and that the difference between an affluent, meat-heavy diet and a vegetarian one ranges between a threefold and eightfold higher need for land (Gerbens-Leenes et al 2002).…”
Section: Sustainable Food Consumption -An Effective Policy Option?mentioning
confidence: 99%
“…The greatest re-spending categories are, in order of magnitude, travel, recreation, food, clothes, and housing. Carlsson-Kanyama et al (2005), on the other hand, find even greater environmental savings than anticipated from a shift to an energy-efficient diet; but this is mainly due to their assumption that 'green' consumers will purchase organic products and incur larger costs than in the original scenario.…”
Section: Consumption and Rebound Effects: State Of The Art And Researmentioning
confidence: 99%
“…Some of the measures adopted by most developed countries include energy use minimization and optimization. Another explored option is renewable energy usage [22], [23]. Regardless of the global threat posed by this phenomenon, Nigerians and the Nigerian government is focused mainly on energy generation, neglecting the aspect of efficient energy utilization by the end users even with the glaring environmental consequences.…”
Section: Climate Change and Energy Usementioning
confidence: 99%
“…cost per cloth load of a washing machine). Along these lines, some authors have considered the effects from the respending of the additional disposable income within the so-called rebound effect framework (Jalas, 2002;Carlsson-Kanyama et al, 2005;Cohen et al, 2005;Takase et al, 2005;Mizobuchi, K., 2008, Nässén andHolmberg, 2009;Druckman et al, 2010;Thomas, 2011;Saunders and Tsao, 2012; Thomas and Azevedo, 2013a;Thomas and Azevedo, 2013b;Chitnis et al, 2013;Yu et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%